(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
Expansive soils, characterized by significant volume fluctuations, pose detrimental effects on pavement performance through swelling and shrinking. A conventional stabilizer Lime has been studied extensively, and this research explores the viability of marble powder, rich in lime, as an alternative stabilizer in situations where pure lime availability is a constraint. Through X-Ray Diffraction tests, mineral composition changes were assessed in Unconfined Compressive Strength (UCS) Test samples, both uncured and 28-day cured, independently stabilized with marble powder and lime. The study evaluated the effects on key factors such as shear strength, swelling potential, and plasticity, influencing the engineering behavior of subgrade soils. Finite Element Analysis (FEA) using PLAXIS software was employed to evaluate vertical and lateral strains, crucial for understanding rutting and pavement fatigue life on this subgrade. Results revealed a 38.80% and 41.13% increase in the fatigue life of the 28-day marble-stabilized subgrade and lime stabilized soil, when compared with zero-day cured unstabilized soil. XRD analysis indicates that marble powder shows limited effectiveness in strength enhancement. Moreover, the rutting life of the 28-day cured marble-stabilized subgrade exhibited 557 times increase, and lime-stabilized subgrade showed 979 times increase compared to uncured unstabilized soil. While the improvement in fatigue and rutting life with marble powder was comparatively less than conventional lime stabilizer, the study concludes that marble powder is a viable stabilizer for expansive soils with low to medium expansiveness. It recommends further investigation of potential combinations of marble powder and lime for effective yet economical soil stabilization.